Coastal Dune Restoration: A Checklist Approach to Site Selection - Della Bella, Andrea; Del Vecchio, Silvia; Fantinato, Edy; Buffa, Gabriella (Land (Basel), 2024)
Coastal dune systems around the world have been severely degraded by human activities, especially in the last century. This has resulted in severe structural and functional damage to these dynamic yet fragile transitional ecosystems and a net loss of important ecosystem services, especially in the face of climate change threats. The implementation of measures for sustainable coastal management and the restoration of degraded ecosystems are urgently needed. In this context, we revised and used several indicators and indices on the geomorphology, biology, and ecology of the dune systems along the Venetian coast to define the current conservation status and assess the feasibility of dune restoration measures. The application of the indices provided important information about the sites and the measures needed to improve the functionality of the coastal dune systems. In addition, the indices provided useful insights for the implementation of management strategies aimed at ensuring the current and future provision of ecosystem services by coastal dune systems and promoting their sustainable use by translating scientific knowledge into management and restoration practices, which has been a bottleneck in ecosystem conservation and restoration so far.